Thirty years of change in HIV incidence among adults in the Kyamulibwa General Population Cohort in rural southwest Uganda, 1989-2021. (April 2023) - Kasamba, Ivan; Mugisha, Joseph; Abaasa, Andrew; Makanga, Ronald; Ruzagira, Eugene; Kaleebu, Pontiano; Seeley, Janet; Newton, Robert; ,
Highlights: We showed a downward trend in HIV incidence over three decades since the early 1990s. The rates of decline in HIV incidence varied over time and by sex and age. The downward HIV incidence trends were concurrent with timely initiation of antiretroviral therapy. Regular HIV testing enabled a higher proportion of people living with HIV who know their HIV status. Abstract: Objectives: To document the changes in HIV incidence over thirty years in Kalungu district, Uganda. Methods: Since 1989, residents aged ≥15 years old have been tested for HIV, and data were collected on HIV risk factors annually and later, biennially in the Kyamulibwa open cohort. In the 2019-2021 survey, people living with HIV self-reported on knowledge of their HIV status, antiretroviral therapy (ART) use, and their most recent viral load data were obtained from health facilities. The HIV seroconversion dates were randomly imputed between the last negative and first positive test dates using a uniform distribution. Results: Among 20, 959 residents who were HIV-negative, 669 seroconverted within 176, 659 person-years. Data showed a downward trend in age-adjusted HIV incidence over 30 years ( P <0.001) even though HIV prevalence steadily increased with ART availability from 2004. Comparing 1990-1992 and 1996-1998, HIV incidence declined by 43% (0.79 to 0.45/100 person-years, P = 0.002). Between 1999 and 2011, the incidence remained stable at 0.49/100 person-years (95% confidence interval: 0.41-0.58) in men but slowly increased in women (average age-adjusted hazard ratio = 1.13 per 3 years, 95% confidence interval: 1.03-1.24; trend P -value = 0.02). After 2011, however, the incidence trends reversed and continued to decline in men and women and in all age groups. Conclusion: Facilitating HIV testing and timely ART initiation, and supporting ART adherence must be emphasized alongside sustainable prevention measures.